Structural Model of Electronic Device Manufacturing Process Quality - Žickis, A. (Elektronika ir Elektrotechnika, 2006)
It is offered to assess the level of manufacturing quality by using quality transfer functions of separate processes. A part of process structure of micro-circuit manufacturing was selected for modeling. Quality transfer function was created for a part of micro-circuit manufacturing process. Flow sizes of circulating ED components during manufacturing processes are considered when calculating this function. Overall micro-circuit quality level calculation technique and integral ED quality model was introduced. Operator for global or partial ED manufacturing quality level optimization was presented. Ill. 1, bibl. 4 (in English; summaries in English, Russian and Lithuanian).